I need to understand the proof of the quadratic equation. I know that it can be done using a completing the square method.  Is it possible to do this quadratic equation proof without completing the square?
asked Apr 8, 2011

## Your answer

 Your name to display (optional): Email me at this address if my answer is selected or commented on: Privacy: Your email address will only be used for sending these notifications. Anti-spam verification: To avoid this verification in future, please log in or register.

## 1 Answer

A quadratic equation in the standard form is given by

ax 2 + bx + c = 0

where a, b and c are constants with a not equal to zero.
...Solve the above equation to find the quadratic fomulas

Given
ax 2 + bx + c = 0

Divide all terms by a
x 2 + (b / a) x + c / a = 0

Subtract c / a from both sides
x 2 + (b / a) x + c / a - c / a = - c / a

and simplify
x 2 + (b / a) x = - c / a

Add (b / 2a) 2 to both sides
x 2 + (b / a) x + (b / 2a) 2 = - c / a + (b / 2a) 2

to complete the square
[ x + (b / 2a) ] 2 = - c / a + (b / 2a) 2

Group the two terms on the right side of the equation
[ x + (b / 2a) ] 2 = [ b 2 - 4a c ] / ( 4a2 )

Solve by taking the square root
x + (b / 2a) = ± sqrt { [ b 2 - 4a c ] / ( 4a2 ) }

Solve for x to obtain two solutions
x = - b / 2a ± sqrt { [ b 2 - 4a c ] / ( 4a2 ) }

The term sqrt { [ b 2 - 4a c ] / ( 4a2 ) } may be written
sqrt { [ b 2 - 4a c ] / ( 4a2 ) } = sqrt(b 2 - 4a c) / 2 | a |

Since 2 | a | = 2a when a > 0 and 2 | a | = -2a when a < 0, the two solutions to the quadratic equation may be written
x = [ -b + sqrt( b 2 - 4a c ) ] / 2 a

x = [ -b - sqrt( b 2 - 4a c ) ] / 2 a

The term b 2 - 4a c which is under the square root in both solutions is called the discriminant of the quadratic equation. It can be used to determine the number and nature of the solutions of the quadratic equation. 3 cases are possible

case 1: If b 2 - 4a c > 0 , the equation has 2 solutions.

case 2: If b 2 - 4a c = 0 , the equation has one solutions of mutliplicity 2.

case 3: If b 2 - 4a c < 0 , the equation has 2 imaginary solutions.

answered Apr 8, 2011 by Level 4 User (9,350 points)
Your c/a value is the product of the roots
Your -b/a value is the sum of your roots

1 answer
1 answer
1 answer
1 answer
1 answer
2 answers